A COMPUTER PROGRAM FOR ANALYZING CONCRETE MIXTURE EXPERIMENTS BASED ON OSADEBE’S REGRESSION MODEL - IFEANYI AGWUOCHA; UCHECHUKWU COLLINS ANYA; CHIOMA TEMITOPE GLORIA AWODIJI; LAWRENCE ETTU (Journal of Engineering Studies and Research)
The Osadebe’s regression model is associated with lots of strenuous mathematical computations. In this research work, a MATLAB based computer program, named MIX-PRE, was formulated for analyzing concrete mixture experiments using the Osadebe’s regression model. It was tested by comparing results obtained from it to previous studies by Anya and Okere. The highest percentage difference between strength results from MIX-PRE and from these studies was about 3%. The % differences for all other parameters studied were close to zero showing little contrast in the predicting ability of MIX-PRE when compared to the direct use of the Osadebe’s regression model.